2019
DOI: 10.1111/aogs.13536
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal detection of esophageal atresia: A systematic review and meta‐analysis

Abstract: Introduction:The primary aim of this systematic review was to quantify the diagnostic performance of ultrasound, magnetic resonance imaging and amniotic fluid analysis in detecting esophageal atresia prenatally. The secondary aim was to explore the accuracy of individual imaging signs in identifying this anomaly.Material and methods: MEDLINE, Embase and Cochrane databases were searched.The quality of studies was assessed using the revised tool for the quality assessment of diagnostic accuracy studies. Summary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 49 publications
(61 reference statements)
1
39
1
1
Order By: Relevance
“…In our study, we found that polyhydramnios was present in 66.66% of cases. A survey conducted in 2019 [23], showed that approximately 58% of patients with tracheoesophageal fistula associated polyhydramnios. Another study by Pardy et al [23] showed that 56.3% of cases with esophageal atresia have an increased amniotic fluid index and associated a small or absent gastric bubble.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that polyhydramnios was present in 66.66% of cases. A survey conducted in 2019 [23], showed that approximately 58% of patients with tracheoesophageal fistula associated polyhydramnios. Another study by Pardy et al [23] showed that 56.3% of cases with esophageal atresia have an increased amniotic fluid index and associated a small or absent gastric bubble.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted in 2019 [23], showed that approximately 58% of patients with tracheoesophageal fistula associated polyhydramnios. Another study by Pardy et al [23] showed that 56.3% of cases with esophageal atresia have an increased amniotic fluid index and associated a small or absent gastric bubble. Analyzing the data obtained in our study, we found that out of the 12 cases diagnosed antenatally with esophageal atresia, in 7 cases, the gastric bubble was absent.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our study, most previous studies did not require the demonstration of an esophageal pouch as a criterion for the prenatal diagnosis of EA/TEF, but rather regarded a persistently small/absent stomach accompanied by polyhydramnios, equally diagnostic. 3,12,[36][37][38] This approach has been shown to be inaccurate. Previous studies show that only a third of fetuses exhibiting a small/absent stomach with polyhydramnios and up to 10% cases of small/absent stomachs without polyhydramnios, have EA/TEF.…”
Section: The Prenatal Diagnosis Of Ea/tef In Twins Compared To Singmentioning
confidence: 99%
“…Esophageal Atresia with or without Tracheo-esophageal Fistula (EA/TEF) occurs in 2.3-2.4 out of 10 000 births. 1,2 Approximately one third of fetuses with EA/TEF are diagnosed prenatally 1,3 . Prenatal detection relies on three sonographic clues: polyhydramnios, absent or small stomach bubble and an esophageal pouch-the dilated blind-end of the upper esophageal segment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation